2022
DOI: 10.1037/pas0001093
|View full text |Cite
|
Sign up to set email alerts
|

Invariance of the Derailment Scale-6: Testing the measurement and correlates of derailment across adulthood.

Abstract: Derailment, a newly mapped construct describing difficulty reconciling perceived changes in identity and selfdirection, offers researchers a unique lens for understanding adjustment. As identity development is a lifelong process, establishing the impartiality of the primary measure for derailment across a broad age range is necessary. Across a cross-sectional sample of emerging, young, and midlife adults (N = 1,420), we tested preregistered hypotheses concerning whether the Derailment Scale-6 (DS-6) demonstrat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 85 publications
(154 reference statements)
0
2
0
Order By: Relevance
“…The focus of the present study is not meant to limit derailment to depression; rather, our introduction of derailment to the counseling literature can act as a springboard for its investigation in relation to other clusters of distress. In addition to established relations between derailment and anxiety (Burrow et al, 2020), derailment negatively relates to future time perspective (Ratner, Burrow, Thoemmes, & Mendle, 2022), an individual difference in the amount of time a person perceives as remaining (Carstensen et al, 1999). People with a more limited future time perspective focus more on the present, and an excessive present orientation may increase risk for substance use (e.g., Barnett et al, 2013; Jochemczyk et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The focus of the present study is not meant to limit derailment to depression; rather, our introduction of derailment to the counseling literature can act as a springboard for its investigation in relation to other clusters of distress. In addition to established relations between derailment and anxiety (Burrow et al, 2020), derailment negatively relates to future time perspective (Ratner, Burrow, Thoemmes, & Mendle, 2022), an individual difference in the amount of time a person perceives as remaining (Carstensen et al, 1999). People with a more limited future time perspective focus more on the present, and an excessive present orientation may increase risk for substance use (e.g., Barnett et al, 2013; Jochemczyk et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…As stated above, the present study is derived from a larger project. The preregistration for the analyses featured in this study, data, and R script can be found on or through the parent project’s repository on the Open Science Framework (https://osf.io/4akjr; direct link to preregistration: https://osf.io/n8kr4; Ratner et al, 2019b, 2022a). All online Supplemental Materials explicitly listed in this article are located on a separate component page of the parent project (https://osf.io/f5sgc/; Ratner et al, 2022b).…”
Section: Methodsmentioning
confidence: 99%